2016
DOI: 10.1002/etc.3342
|View full text |Cite
|
Sign up to set email alerts
|

A test of the additivity of acute toxicity of binary‐metal mixtures of ni with Cd, Cu, and Zn to Daphnia magna, using the inflection point of the concentration–response curves

Abstract: Mixtures of metals are often present in surface waters, leading to toxicity that is difficult to predict. To provide data for development of multimetal toxicity models, Daphnia magna neonates were exposed to individual metals (Cd, Cu, Ni, Zn) and to binary combinations of those metals in standard 48-h lethality tests conducted in US Environmental Protection Agency moderately hard reconstituted water with 3 mg dissolved organic carbon (DOC)/L added as Suwannee River fulvic acid. Toxicity tests were performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 34 publications
2
45
1
Order By: Relevance
“…The values of 48h-LC 50 of D. magna and Ceriodaphnia.dubia to Zn were 928 and 102 -130 µg/L, respectively (Naddy et al, 2015;Traudt et al, 2016) at moderately hard water (in the test with D. magna) and hard water (in the test with C. dubia) revealed that D. lumholtzi was more sensitive to Zn than D. magna but less sensitivity to Zn than C. dubia. This record is in line with previous investigation revealing the high sensitivity of D. lumholtzi to trace metals (Dao et al, 2016).…”
Section: Acute Testmentioning
confidence: 92%
See 1 more Smart Citation
“…The values of 48h-LC 50 of D. magna and Ceriodaphnia.dubia to Zn were 928 and 102 -130 µg/L, respectively (Naddy et al, 2015;Traudt et al, 2016) at moderately hard water (in the test with D. magna) and hard water (in the test with C. dubia) revealed that D. lumholtzi was more sensitive to Zn than D. magna but less sensitivity to Zn than C. dubia. This record is in line with previous investigation revealing the high sensitivity of D. lumholtzi to trace metals (Dao et al, 2016).…”
Section: Acute Testmentioning
confidence: 92%
“…Vardia et al (1998) and Chishty et al (2012) reported the 48h-LC 50 values of D. lumholtzi tested with Zn dissolved in tap water were 2290 and 2300 µg/L, respectively. The median effective (immobilized) concentration (48h-EC 50 ) values of four different metals (Cd, Cu, Ni, Zn) to Daphnia magna were much different and the toxicity order of those metals to the tested species was Cd > Cu > Zn > Ni (Traudt et al, 2016). Besides, Cu was more toxic than some other metals such as Ni, Zn and chromium (Cr) to the two cladocerans, Moina macropora and D. magna (Biesinger and Christensen, 1972;Wong, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Because organisms of different developmental stages may differ in their sensitivity to a chemical, many regulatory agencies (USEPA 2002;OECD 2004) specify that acute toxicity tests should be started with D. magna younger than 1 day old. However, we have observed relatively high variability in the toxicity of Cd and Zn to D. magna neonates Traudt et al 2015) and have demonstrated that this variablity is at least partly caused by major changes in sensitivity to the metals even within their first day postbirth (Traudt et al 2016). This methodologically induced variability can have important consequences, especially for predictions of metal-mixture toxicity when using results from individual-metal tests.…”
mentioning
confidence: 84%
“…We previously exposed D. magna to binary and ternary mixtures of Cd, Cu, Ni, and Zn in 48-h, static, nonrenewal lethality tests following USEPA-recommended procedures Traudt et al 2015). We observed high variability in mortality in the binary and ternary mixtures that contained either Cd or Zn but relatively lower variability in mixtures containing Cu or Ni.…”
mentioning
confidence: 99%
“…Because organisms of different developmental stages may differ in their sensitivity to a chemical, many regulatory agencies (USEPA 2002; OECD 2004) specify that acute toxicity tests should be started with D. magna younger than 1 day old. However, we have observed relatively high variability in the toxicity of Cd and Zn to D. magna neonates (Meyer et al 2015; Traudt et al 2015) and have demonstrated that this variablity is at least partly caused by major changes in sensitivity to the metals even within their first day postbirth (Traudt et al 2016). This methodologically induced variability can have important consequences, especially for predictions of metal-mixture toxicity when using results from individual-metal tests.…”
mentioning
confidence: 92%